PENGARUH TERAPI KOMPRES HANGAT TERHADAP PENURUNAN NYERI SENDI OSTEOARTHRITIS PADA LANSIA DI POSYANDU LANSIA PUSKESMAS PANDIAN SUMENEP - Mujib Hannan; Emdat Suprayitno; Hesti Yuliyana (Wiraraja Medika : Jurnal Kesehatan, 2019)
Along with the aging process, the body will experience various health problems. One of them osteoartrisis which is a disease of bones and joints that occur due to aging process. The purpose of this study was to study the effect of warm water compress therapy on the reduction of osteoarthritis joint pain in elderly at posyandu elderly puskesmas Pandian Sumenep. The type of research is Pre Experimental, where the population amounted to 40 people and the sample amounted to 32 people with elderly characteristics who experience osteoarthritis joint pain. Sampling technique used is Type Probability sampling that is Simple Random Sampling. Data collection methods used were interviews and questionnaires. Presentation of data using pie chart and characteristic distribution table with T paired statistical test. The results showed that more than half had osteoarthritis joint pain with moderate pain scale of 22 elderly (68.7%). Based on the result of T paired test, there is influence between warm water compress therapy to decrease osteoarthritis joint pain in elderly (ρ = 0,000 <α = 0,05). Osteoarthritis pain in elderly in Puskesmas Pandian Sumenep mostly due to the activity of many or excess. Advice for health services to make warm compress therapy as a self-directed nursing intervention in treating joint pain patients with osteoarthritis.